(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In today’s global world, English serves not only as a tool for international communication but also holds significant importance in the fields of education, business, technology, and science. Therefore, the ability to communicate fluently and effectively in English is considered one of the main goals for every language learner. This article analyzes the key methods and approaches aimed at developing oral and written communication skills in English.